Professional development: a mixed methods study of Masters of Public Health alumni - Baron-Epel, Orna; Douvdevany, Yana; Ivancovsky-Wajcman, Dana; Barach, Paul; Bashkin, Osnat; Czabanowska, Katarzyna; Dopelt, Keren; Davidovitch, Nadav; Jakubowski, Szczepan; MacLeod, Fiona; Malowany, Maureen; Okenwa-Emegwa, Leah; et al. (Frontiers in Public Health, 2024)
We examined the perceptions of the Masters in Public Health (MPH) degree graduates regarding their personal competencies, job performance and professional development using a mixed methods, explanatory sequential design, as part of a capacity-building in higher education project "Sharing European Educational Experience in Public Health for Israel" (SEEEPHI). A cross-sectional, selfadministered questionnaire survey of the Haifa School of Public Health alumni was performed with 127 MPH graduates. This was followed by 24 in-depth interviews with alumni from the same sample. The sample included 74.8% females and a mean age of 40.7 years, 35% of alumni agreed that the MPH degree helped them attain a promotion in their present position (in rank or salary) and 63.8% felt that the degree helped them improve their job performance and contribute to their current workplace. Most (80.3%) alumni reported that they did not change jobs after graduation. The interview themes revealed that the MPH contributed to their personal and professional lives, provided them with a holistic view of public health and health systems and improved their in-depth scientific skills. The main reported barriers to professional development included missing core competencies, low salaries, and a lack of information regarding suitable jobs. Surprisingly, an MPH was not a requirement for some public health sector jobs. Alumni reported that the MPH degree contributed to improving many graduates' careers and satisfaction levels and to build their leadership competencies in public health. However, there is a clear lack of coordination between the academic curriculum and the jobs available for alumni, hindering better alumni professional development. Regular discussions, information sharing and curriculum refinements between MPH program leaders and health sector leaders might help address many of the concerns of the MPH degree graduates.